Examining kidney donation in Nigeria: a mixed methods study of family members’ knowledge, perceptions, information needs and decision-making - Manmak Mamven; Oluseyi Ademola Adejumo; Imuetinyan Rashida Edeki; Dapo Sunday Oyedepo; Stanley Chidozie Ngoka; Alhaji Abdu; Moses Tari Tuko; Lawrence Adedeji Adeyeye; Umar Loskurima; Ayodeji Fasaanu; Nwokedi Chinedu Madu; Dorcas Angbazo; et al. (BMC Nephrology)
Abstract Background A major challenge of transplantation is the unavailability of organs. For a successful transplantation process, awareness and negative attitudes among potential donors need to be sought for and addressed. Our objective was to examine the knowledge, perception and information needs of family members of patients with chronic kidney disease (CKD) in Nigeria and factors associated with their likelihood to decide to donate a kidney. Methods This was a convergent parallel mixed method study that obtained information from family members of patients with CKD in Nigeria. Ordinal logistic regression was used to determine factors associated with the likelihood of donation. Thematic analysis was used for the qualitative analysis. Results Three hundred and six respondents with a mean age of 41.2 ± 12.9 years participated in the quantitative survey. About 30% of participants were not familiar with the concept of kidney donation; 63% had never sought information about kidney donation; about 75% felt inadequately informed about the risks, benefits, and requirements of kidney donation. About 26% of participants were unlikely to consider donating a kidney to a family member with CKD. The majority expressed medical risk (47%) as their primary concern with donation. The age group of respondents (OR 0.48, 95% CI 0.239–0.967, P = 0.04), parent/child relationship, (OR 2.42, 95%CI 1.198–4.886, P = 0.01), awareness of the suitable medical factors for donation (OR 2.07, 95%CI 1.127–3.796, P = 0.02), and provision of support or counsel to donors (OR 3.89, 95%CI 1.576–9.638, P = 0.003), were independently associated with decisions to donate. The qualitative analysis identified personal, socio-cultural, religious and psychological factors that could influence willingness to donate. Conclusion This study identified factors that influenced donations and brought to the fore the need to adequately educate and provide support for potential kidney donors. Clinical trial number Not applicable.